The Influence of Transformational Leadership and Motivation on Work Discipline and Its Impact on Employee Performance PPNPN ATR/BPN Bekasi City - Enggar Pratama Sari; Subagja, Iwan Kurniawan; Samosir, Partogi Saoloan (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
This study aims to test and analyze 1). the effect of transformational leadership on work discipline; 2). the effect of motivation on work discipline; 3). the effect of transformational leadership on employee performance; 4). the effect of motivation on employee performance; 5). the effect of work discipline on employee performance; 6). the effect of transformational leadership on work discipline and its impact on employee performance; 7). the effect of motivation on work discipline and its impact on employee performance. The research was conducted on PPNPN ATR / BPN Bekasi City employees with a research sample of 87 respondents. The sampling technique used simple random sampling technique. Data analysis methods using descriptive analysis and path analysis. The results showed that: 1). There is an influence of transformational leadership on work discipline; 2). There is an influence of motivation on work discipline; 3). There is no effect of transformational leadership on employee performance; 4). There is no influence of motivation on employee performance; 5). There is an influence of work discipline on employee performance; 6). There is an effect of transformational leadership on work discipline and its impact on employee performance; 7). There is no effect of motivation on work discipline and its impact on employee performance